XQuery kick start - McGovern, James, 1967- (Kick Start Ser., 2004)
XQuery Kick Start delivers a concise introduction to the XQuery standard, and useful implementation advice for developers needing to put it into practice. The book starts by explaining the role of XQuery in the XML family of specifications, and its relationship with XPath. The authors then explain the specification in detail, describing the semantics and data model, before moving to examples using XQuery to manipulate XML databases and document storage systems. Later chapters discuss Java implementations of XQuery and development tools that facilitate the development of Web sites with XQuery. This book is up to date with the latest XQuery specifications, and includes coverage of new features for extending the XQuery language.